The Effect of Supervision, Employee Engagement, and Work Experience on Employee Performance in a Government Tax Office - Heni Kartika Indah Purwati; Kuswandi Kuswandi; Sri Rahayu; Rifda Fitrianty (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The effectiveness of public institution employees is vital in ensuring high-quality service delivery, but obstacles like supervision, engagement, and work environment can impede success. This research examines how Supervision, Employee Engagement, and Work Experience impact Employee Performance at the Pratama Surabaya Tegalsari Tax Office through both individual and combined analysis. Given the importance of employee performance in government agencies for effective public service delivery, this investigation is essential. The study adopts a quantitative methodology utilizing multiple linear regression to assess variable relationships. A census sampling approach was implemented, incorporating all 77 employees from the tax office as participants. Findings reveal that Employee Engagement and Work Experience individually demonstrate significant positive effects on performance, whereas Supervision shows a positive but non-significant impact. When examined collectively, all three variables significantly affect employee performance. The coefficient of determination demonstrates that the model accounts for a considerable proportion of performance variation. These findings shed light the importance of enhancing employee engagement and leveraging work experience as strategic efforts to improve organizational performance.